PENERAPAN RESTORATIVE JUSTICE TERHADAP TINDAK PIDANA PENGANIAYAAN DI KEPOLISIAN SEKTOR BAWOLATO KABUPATEN NIAS - Lafau, Firman Fati Zaya (LPPM Universitas Nias Raya, 2025)
Restorative justice or restorative justice is the resolution of criminal cases involving the perpetrator, victim, family of the perpetrator/victim, and other related parties to jointly seek a fair solution by emphasizing restoration to the original condition, and not retaliation. The aim of this research is to find out how Restorative Justice is implemented in the crime of ill-treatment in the Bawolato Police Sector, Nias Regency. The type of research used is sociological or empirical legal research, namely examining applicable legal provisions based on existing facts in a society. Data collection was carried out using primary data, secondary data and tertiary data. obtained from secondary legal materials. The data analysis used is qualitative data analysis. Qualitative data analysis is carried out together with the data collection process. Based on the research findings and discussion, it can be concluded that the application of restorative justice to criminal acts of abuse in the Bawolato Sector Police, Nias Regency is the best solution offered by the Bawolato Sector Police, Nias Regency in resolving a crime in a family manner. This settlement provides benefits to both parties in terms of time, penalties and costs. For its implementation, the Police will present both parties to provide direction and make peace. If they agree, the police will punish the perpetrator according to the agreement. Then, both parties make a written agreement which functions as a binding promise for both parties to be used in the future if one of them violates the agreement.